FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STRES KERJA PADA PERAWAT KAMAR BEDAH DI INSTALASI BEDAH SENTRAL RSUD K.R.M.T WONGSONEGORO SEMARANG - Nadia Fuada; Ida Wahyuni; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Every job always has risks and potential dangers that could affect the workers, One of them is psychic disorder. Psychological disorders that are not addressed can lead to work stress. The survey results of the Indonesian National Nurses Association (PPNI) in 2006 stated that 50.9% of Indonesian nurses experience job stress due to workload, working conditions and unfair salary. The aim of this study was to find the related factors of work stress on surgical nurse. The dependent variable is work stress while the independent variables are age, gender, year of service, work shifts, physical workload, mental workload, work routine, individual role in organization, career development, and work relationship. This type of this research is explanatory research with cross sectional approach.The population of this research is surgical nurse with a total of 37 people. The sample in this study were drawn from the total population. The process of data collection was using questionnaires and physical work load measurement with Pulsemeter. The data were analyzed with Chi-Squre correlation test. The correlating variables are physical workload, mental workload, individual role in organization, and career development. While the non-correlating variables are age, gender, years of service, work shifts, work routine, and work relationship.